The principal's strategy for developing teacher professionalism at junior high school: A case study - Jumilati, Siti; Supandi; Harjito (Al-TA'DIB: Jurnal Kajian Ilmu Kependidikan, 2026)
This study aims to analyze principals' strategies in developing teacher professionalism in public junior high schools in Pemalang Regency. The study used a qualitative approach with a case study design, involving purposively selected principals and teachers. Data were collected through interviews, observations, and documentation, then analyzed thematically. The results showed that principals implemented data-driven strategies through participatory planning, clinical academic supervision, digital mentoring, and strengthening learning communities that encourage collaboration and reflection. This implementation encouraged the use of project-based learning and digital media. However, a gap remains between academic outcomes stipulated in school policies and classroom learning practices, caused by teachers' limited ability to develop higher-order thinking skills-oriented assessments and limited resources. These findings emphasize the importance of strengthening assessment capacity and ongoing collaborative coaching.